2018
DOI: 10.3389/fphar.2018.00132
|View full text |Cite
|
Sign up to set email alerts
|

The Psychedelic Debriefing in Alcohol Dependence Treatment: Illustrating Key Change Phenomena through Qualitative Content Analysis of Clinical Sessions

Abstract: Research on the clinical applications of psychedelic-assisted psychotherapy has demonstrated promising early results for treatment of alcohol dependence. Detailed description of the content and methods of psychedelic-assisted psychotherapy, as it is conducted in clinical settings, is scarce.Methods: An open-label pilot (proof-of-concept) study of psilocybin-assisted treatment of alcohol dependence (NCT01534494) was conducted to generate data for a phase 2 RCT (NCT02061293) of a similar treatment in a larger po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(112 citation statements)
references
References 48 publications
(70 reference statements)
7
91
0
6
Order By: Relevance
“…In many studies, participants experienced significant relief from the disorder they were treated for, including reductions in eating disorder-related thoughts and symptoms, PTSD symptoms, anxiety, depression, and substance use. Reductions in withdrawal and reduced (in some cases completely vanished) craving were mentioned by participants in all studies on SUDs [77,78,83,86,89,90]. Remarkably, decreased drug, alcohol, and medication use were also reported in studies with MDMA, ayahuasca and psilocybin that did not deal directly with substance use [53,80,87].…”
Section: Symptom Reliefmentioning
confidence: 90%
See 3 more Smart Citations
“…In many studies, participants experienced significant relief from the disorder they were treated for, including reductions in eating disorder-related thoughts and symptoms, PTSD symptoms, anxiety, depression, and substance use. Reductions in withdrawal and reduced (in some cases completely vanished) craving were mentioned by participants in all studies on SUDs [77,78,83,86,89,90]. Remarkably, decreased drug, alcohol, and medication use were also reported in studies with MDMA, ayahuasca and psilocybin that did not deal directly with substance use [53,80,87].…”
Section: Symptom Reliefmentioning
confidence: 90%
“…All articles were published between 2014 and 2019. Where reported, respondents' ages ranged from 21 to 67 years, and the number of included subjects ranged from 4 [77] to 22 [78,79]. Studies were heterogeneous in terms of substances, population/mental disorders, contexts, and qualitative research methodologies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is mounting evidence that the positive long-term effects of psychedelic therapy are mediated by the quality of the acute psychedelic experience (44)(45)(46)(47). Qualitative interviews with patients have shown that avoidance and acceptance are often central themes of their psychedelic experiences (13,(48)(49)(50)(51), and patients commonly report transient episodes of struggle with intense aversion. These challenging experiences 1 (42,52,53) are often characterized by extreme fear or panic, and can involve frightening imagery, unsettling body sensations, and the apprehension of immediate threat.…”
Section: Avoidance and Acceptance In Psychedelic Therapymentioning
confidence: 99%